Réduction du temps de travail: mode d'emploi - Charest, Jean (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Réduction du temps de travail: mode d'emploi," by Jean-Pierre Mongrand.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working hours